Heterozygous Genetic Variants in Autosomal Recessive Genes of the Leptin-Melanocortin Signalling Pathway Are Associated With the Development of Childhood Obesity - Šket, Robert; Kotnik, Primož; Bizjan, Barbara Jenko; Kocen, Valentina; Mlinarič, Matej; Tesovnik, Tine; Debeljak, Maruša; Battelino, Tadej; Kovač, Jernej (Frontiers in Endocrinology, 2022)
Monogenic obesity is a severe, genetically determined disorder that affects up to 1/1000 newborns. Recent reports on potential new therapeutics and innovative clinical approaches have highlighted the need for early identification of individuals with rare genetic variants that can alter the functioning of the leptin-melanocortin signalling pathway, in order to speed up clinical intervention and reduce the risk of chronic complications. Therefore, next-generation DNA sequencing of central genes in the leptin-melanocortin pathway was performed in 1508 children and adolescents with and without obesity, aged 2-19 years. The recruited cohort comprised approximately 5% of the national paediatric population with obesity. The effect size of rare variants in the leptin-melanocortin signalling pathway on longitudinal weight gain between carriers and non-carriers was estimated. In total, 21 (1.4%) participants had known disease-causing heterozygous variants (DCVs) in the genes under investigation, and 62 (4.1%) participants were carriers of rare variants of unknown clinical significance (VUS). The estimated frequency of potential genetic variants associated with obesity (including rare VUS) ranged between 1/150 (VUS and DCV) and 1/850 (DCV) and differed significantly between participants with and without obesity. On average, the variants identified would result in approximately 7.6 kg (7.0-12.9 kg at the 95th percentile of body weight) (girls) and 8.4 kg (8.2-14.4 kg) (boys) of additional weight gain in carriers at age 18 years compared with subjects without obesity. In conclusion, children with a genetic predisposition to obesity can be actively identified and may account for more than 6% of cases. Early identification of genetic variants in the LEPR, PCSK1, POMC, MC3R and MC4R genes could reduce the societal burden and improve the clinical management of early severe childhood obesity.